Win-win partnering in building and civil engineering delegate information : 15 June 1998 at One Great George Street Conference Centre (Thomas Telford, 1998)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held on 15 June 1998.
Keywords: Construction industry -- Management -- Congresses.; Teams in the workplace -- Congresses.; Engineering -- Management -- Congresses.; Strategic alliances (Business) -- Congresses.; elektronické knihy; electronic books